Land regularization in Piauí: Analysis of the Regularize Program in implementing the right to housing (Research, Society and Development, 2023)
This study addresses land regularization in Piauí, focusing on the effectiveness of the Regularizar Program in guaranteeing the right to housing. The research aims to investigate the legal and operational mechanisms adopted by the program, and is based on a bibliographical approach. The research aims to answer the central question: what mechanisms are used by the Regularization Program of the State of Piauí to implement the fundamental right to housing? To this end, the work is divided into three chapters that cover everything from legal and principled frameworks to an in-depth analysis of the aforementioned program. The urgency of the issue lies in the constant violation of fundamental rights in irregular settlements and the need for legislative and strategic reformulations that can mitigate this problem. The results aim to provide input for future legislative and political initiatives, given the recurrent violation of rights in irregular settlements. The results indicate that, despite legal advances, there are still normative and structural challenges to be overcome to realize the right to decent housing.